The impact of political instability on the developmental direction in Iraq - Hanan Abdul Khader Al-Moussawi; Abdul Wahab Mohammed Jawad Al-Moussawi; Haider Nema Bakhit (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
The truth, which has been around a lot are no different: that in an economy can be practiced changes and political instability and successive crises negative impact on the development plans, and this applies to the case of the Iraqi economy, and reinforcing it is the repetition of developmental failures taking place, because of the political instability experienced Since A long time ago. the wrong economic decisions it making things more complicated, is studied that is not based or based on the true economic fundamentals are consistent with all the conditions experienced by and experienced by the country, as there is a distinct lack of development plan integrated aspects mimic reality, or are compatible with economic and social environment in Iraq. Incomes in a series of endless wars (external and internal) and take different forms from the departments of government and leadership of the variety, and the difficulty of confrontation for all terrorist challenges, it was the outcome of it all falling into the trap of the almost total destruction of infrastructure, structural imbalance and productive, rates high unemployment and widespread poverty among the community members, and exacerbation of administrative and financial corruption in all its forms in the state institutions and the basic pillars, which meant each case, the face of a serious fact, a weakness of the fundamental economic pillars, leading to any development process successful Iraq